Indonesia-Malaysia Cooperation In Handling Illegal Immigrants: From The Perspective of International Law and Human Rights Protection - Azkia Fathia Kirana Sopian; Otong Syuhada; Rani Dewi Kurniawati (JURNAL ILMIAH LIVING LAW, 2026)
The phenomenon of illegal immigrants in Southeast Asia, particularly in the Indonesia-Malaysia corridor, poses serious challenges related to legal, security, and human rights issues. The complexity of this problem arises from differences in national regulations, weak cross-border surveillance, and high economic pressures that drive irregular migration. This study aims to analyze the extent to which bilateral cooperation between Indonesia and Malaysia in handling illegal immigrants is in accordance with international law and human rights protection principles. The method used is a normative juridical approach, examining international legal instruments such as the International Convention on the Protection of the Rights of All Migrant Workers and Members of Their Families (1990), ICCPR, ICESCR, and various bilateral Memoranda of Understanding (MoU) between the two countries. The results of the study show that, normatively, Indonesia-Malaysia cooperation has referred to international legal standards that emphasize humane treatment, the principle of non-refoulement, and the protection of the basic rights of migrants. However, operationally, its implementation still faces obstacles in the form of weak inter-agency coordination, limited resources, and a lack of independent oversight. These conditions have led to continued human rights violations, particularly in the form of arbitrary detention and limited access to basic services for undocumented migrants. Thus, strengthening monitoring mechanisms, training officers, and involving international organizations are necessary for this cooperation to be more effective, humane, and sustainable in accordance with the principles of international law.